Forensic psychiatry and Covid-19: accelerating transformation in forensic psychiatry. (21st June 2021) - Kennedy, H. G.; Mohan, D.; Davoren, M.
Abstract: Swift medically led scientifically informed responses to the Covid-19 epidemic nationally have been demonstrably superior to other, non-scientific approaches. In forensic psychiatry and across all psychiatric services, urgent and clinically led responses have underlined redundancies and confusions in the governance of mental health services and a vacuum in policy makers. For the future, a greater emphasis on services for patients with schizophrenia and other severe, enduring mental disorders must aim at reducing standardised mortality ratios, managing risk of violence and improving hard outcomes such as symptomatic remission, functional recovery and forensic recovery of autonomy. This will require more use of information technology at service level and at national level where Scandinavian-style population-based data linkage research must now become legally sanctioned and necessary. A national research and development centre for medical excellence in forensic psychiatry is urgently required and is complimentary to and different from quality management.